Oxide‐Mediated Formation of Chemically Stable Tungsten–Liquid Metal Mixtures for Enhanced Thermal Interfaces. Issue 44 (16th September 2019) - Kong, Wilson; Wang, Zhongyong; Wang, Meng; Manning, Kenneth C.; Uppal, Aastha; Green, Matthew D.; Wang, Robert Y.; Rykaczewski, Konrad
Abstract: Modern microelectronics and emerging technologies such as wearable devices and soft robotics require conformable and thermally conductive thermal interface materials to improve their performance and longevity. Gallium‐based liquid metals (LMs) are promising candidates for these applications yet are limited by their moderate thermal conductivity, difficulty in surface‐spreading, and pump‐out issues. Incorporation of metallic particles into the LM can address these problems, but observed alloying processes shift the LM melting point and lead to undesirable formation of additional surface roughness. Here, these problems are addressed by introducing a mixture of tungsten microparticles dispersed within a LM matrix (LM‐W) that exhibits two‐ to threefold enhanced thermal conductivity (62 ± 2.28 W m −1 K −1 for gallium and 57 ± 2.08 W m −1 K −1 for EGaInSn at a 40% filler volume mixing ratio) and liquid‐to‐paste transition for better surface application. It is shown that the formation of a nanometer‐scale LM oxide in oxygen‐rich environments allows highly nonwetting tungsten particles to mix into LMs. Using in situ imaging and particle dipping experimentation within a focused ion beam and scanning electron microscopy system, the oxide‐assisted mechanism behind this wetting process is revealed. Furthermore, since tungsten does not undergo room‐temperature alloying with gallium, it is shown that LM‐W remains a chemically stable mixture. Abstract : The formation of a chemically stable mixture of tungsten microparticles and liquid metal (LM) with 2–3 times enhanced thermal conductivity (60 W m −1 K −1 ) and easy‐to‐apply paste consistency is enabled through blending in an oxygen‐rich environment. In situ imaging reveals how the adhesion of nanoscale gallium oxide flakes on the LM‐phobic particles enables their wetting and paste formation.